A Randomized Controlled Trial of the Influence of Intermittent Versus Continuous Bladder Catheterization on Labor Outcomes. Issue 1 (June 2015) - Wilson, Barbara
<x xml:space="preserve">Abstract</x> Paper Presentation Objective To determine the influence of continuous urinary catheterization (CC) versus intermittent catheters (ICs) (only as needed) on duration of second stage of labor, incidence of postpartum urinary tract infections (UTIs), and the likelihood of cesarean births. Design Randomized controlled trial. Setting Large medical center in the Southwest. Sample English speaking primiparas > 37‐weeks gestation with low‐risk vertex singletons who requested epidural analgesia were eligible for participation. The final sample size included 120 participants: 55 in the CC group and 65 in the IC group. Methods Women were randomized to receive either IC or CC prior to epidural placement, and cervical status was documented. Results There was a significantly increased likelihood of cesareans in women who had CCs (p < .01). The overall cesarean rate in the CC group was 28.8% versus 9.9% in the IC group. No differences were noted in length of labor, and the overall incidence of UTIs in both groups was low. Conclusion/Implications for Nursing Practice Intermittent catheters only as needed appear to be best practice for bladder management in laboring women with epidurals.